Theoretical limits of the increase of radiative heat transfer by increased surface areas of radiant tubes. (5th February 2021) - Lenz, Wolfgang; Brykarczyk, Daniel; Pfeifer, Herbert; Neumann, Andreas; Bambach, Markus
Highlights: Increase of area of radiating surfaces like radiant tubes by structuring is possible. Effect of increased surfaces areas is limited by theoretical limits. For relevant emissivities, the effect of increased surface areas close to unusable. Abstract: Gas fired industrial furnaces with protective gas atmospheres use radiant tubes, muffles, or similar devices to separate the furnace atmospheres from combustion off gases. Heat is transferred to the furnace mainly by radiation from the tubes surfaces. Some commercial attempts were made to increase the surface areas of radiant tubes by adding bulged structures to its surface to increase the transferred heat flow rate. Considering basic equations of radiative exchange, it can be shown that increasing the surface area of radiation sources is not an effective measure to increase heat transfer. This article shows the theoretical limits for the improved transferred heat flow rates by increasing radiating surfaces. Practically, the actual limits are even below those theoretical limits.